A decision support system for sustainable energy supply combining multi-objective and multi-attribute analysis: An Australian case study - Mattiussi, A.; Rosano, Michele; Simeoni, P. (Elsevier, 2014)
A framework for an energy supply decision support system (DSS) for sustainable plant design and production ispresented in this paper, utilising an innovative use of multi-objective and multi-attribute decision-making(MODM, MADM) modelling together with impact assessment (IA) of the emission outputs. The mathematicalmodel has been appliedwithin an eco-industrial park (EIP) setting and includes three steps. First, an assessmentof the total EIP emissions' inventory and impacts is conducted; the second step, focusing on the sustainabilitybenefits of combined heating and power (CHP) plants and photovoltaic technologies, developed a multiobjectivemathematical model including both economic and environmental objectives in a Pareto-frontieroptimisation analysis. Four different scenarios involving combinations of CHP plants (internal combustion engine,gas turbine, micro-turbines and fuel cells) and two types of PV plant (monocrystalline and polycrystalline)were evaluated. The third step utilises a MADM methodology – the analytic hierarchy process (AHP) – forselecting the best alternative among the Pareto-frontier efficient solutions. This model has been applied to acase study of an EIP located in Perth (Kwinana Industrial Area—KIA),Western Australia.